Contemporary debates in philosophy of mind - McLaughlin, Brian P.; Cohen, Jonathan D. 1971- (Contemporary debates in philosophy, 2021)
Contemporary Debates in Philosophy of Mind showcases the leading contributors to the field, debating the major questions in philosophy of mind today. Comprises 20 newly commissioned essays on hotly debated issues in the philosophy of mind. Written by a cast of leading experts in their fields, essays take opposing views on 10 central contemporary debates. A thorough introduction provides a comprehensive background to the issues explored. Organised into three sections which explore the ontology of the mental, nature of the mental content, and the nature of consciousness.